Local Cultural Values in Income Accounting: A Study of Gorontalo Carriage Drivers - Thalib, Mohamad Anwar (Journal of Accounting Inquiry, 2024)
Purpose: This study aims to construct income accounting practices that integrate the local cultural values of the Gorontalo community. It addresses the need to preserve and incorporate cultural and spiritual dimensions into accounting frameworks, emphasizing the significance of cultural heritage in shaping accounting practices. Methodology: The research adopts a spiritual (Islamic) paradigm and employs an Islamic ethnomethodological approach. Data analysis is conducted in five stages: charity, knowledge, faith, revelation information, and courtesy. Findings: The study reveals that Gorontalo carriage drivers utilize a leasing system for income generation, guided by local wisdom. The principle of gratitude is central to this system, reflecting the cultural adage diila o'onto, bo wolu-woluwo, which underscores the balance between visible and invisible pursuits in life. This demonstrates that their accounting practices transcend material calculations, integrating cultural and religious values.  Novelty: This research introduces a novel accounting concept that merges local cultural values and spirituality into practical accounting frameworks. It highlights the importance of cultural preservation in accounting and offers a new perspective for exploring the interplay between local wisdom and financial systems.